“Mobilização e Encantarias” - XII Congresso Brasileiro de Agroecologia/CBA - Almeida Souza, Natália; Silva, Generosa; Albuquerque Ferrer Pinheiro, Luísa; Bezerra, Islandia (Revista Brasileira de Agroecologia, 2022)
Editorial